WHITLEBLOWING INTENTION SEBAGAI BAGIAN DARI ETIKA ISLAM DITINJAU DARI INTENSITAS MORAL, ORIENTASI ETIKA RELATIVISME DAN RELIGIUSITAS - Puspitosari, Indriyana (Jurnal Iqtisaduna, 2019)
Wrongdoing can occur in every organization. When an individual knows the wrongdoing, there is an option for the individual to leave it or report it. The individual's intention to report a wrongdoing can be influenced by factors related to themself, organization and environment.The purpose of this study is to examine the factors in their intention to report violations which consist of ethical orientation factors of relativism, moral intensity and religiosity. The object in this study is IAIN Surakarta Accounting students.The results of this study indicate that the variables of ethical orientation and religiousity have a significant influence on the intention to report wrongdoing. While the moral intensity variable does not affect the whistleblowing intentions.